Dinamika Pemenuhan Hak dan Kewajiban dalam Keluarga Muslim Pekerja Migran di Sutojayan, Blitar dalam Tinjauan Normatif-Sosiologis - Faidati, Ashima; Maratus, Nuril Farida (Kodifikasia, 2025)
This study aims to analyze the dynamics of fulfilling rights and obligations within Muslim migrant worker families in Sutojayan District, Blitar, East Java. The research is grounded in the reality of shifting roles and sociological challenges faced by migrant families, particularly in maintaining a balance between material, spiritual, and emotional aspects. Employing a normative-sociological approach and qualitative methods, data were collected through in-depth interviews and participatory observation, then analyzed thematically. The findings indicate that the resilience of Muslim migrant families is shaped by their ability to adapt to role transitions, maintain emotional support across distances, and internalize religious and local cultural values to preserve family harmony.